Integrating STEM-Qur’an Approach into Digital Flipbook-Based Teaching Materials: A Validation Study - Yusri Handayani; Rahmawati Rahmawati; Salwa Rufaida; Fahrunnisa Fahrunnisa; Widiasih Widiasih (Postgraduate, University of Mataram, 2025)
This study addresses the limited availability of instructional media that integrate scientific content with spiritual values in physics education. It aims to develop and validate digital flipbook-based teaching materials for Basic Physics using the STEM-Qur’an (STEMQ) approach. The objective is to produce educational content that combines scientific accuracy, interactive digital design, and the integration of Qur’anic principles to foster ethical and holistic learning. A descriptive validation method was applied involving expert judgment to evaluate two main dimensions: content validity and media quality. Content evaluation focused on curriculum alignment, conceptual accuracy, language clarity, instructional structure, and STEMQ integration. Media validation assessed digital layout, implementation practicality, and technological functionality. Data were analyzed using the Gregory Index, resulting in a coefficient of 0.90 for content and 0.83 for media, indicating high validity. The findings confirm that the flipbook is pedagogically sound, technologically usable, and culturally relevant for Islamic science education. This validated model supports the integration of empirical inquiry with Qur’anic values and offers a framework for future development and classroom application